PENDAMPINGAN TPQ DENGAN OPTIMALISASI BACA TULIS AL-QUR’AN UNTUK MENCIPTAKAN GENERASI QUR’ANI - Cholifatul Azizah; Allifia Hariaji; Farih Alfaza; Asnal Mala; Eli Masnawati; Mirza Elmy Safira; Alfiatul Izzati Irawan; Shinta Maulidia Safitri; Masfufah; Yuliastutik; Nelud Daraajatul Aliyah (Abdi Jurnal Publikasi, 2024)
Islamic religious education has an essential role in shaping the character and morals of the younger generation, especially in the context of Indonesian society, which is predominantly Muslim. One important element of religious education is the teaching of the Koran, which is carried out at the Al-Qur'an Education Park (TPQ). However, the quality of teaching at TPQ often faces significant challenges, including low reading and writing skills of the Qur'an among students. TPQ in rural areas sometimes still experience difficulties in implementing the method (Rahmawati, 2018). This problem can be caused by several factors, including lack of resources, and limited study time. A more interactive and personal teaching approach will be able to improve Al-Qur'an reading skills (Zulkarnain, 2017). The program